HIGH-PRESSURE LUMINESCENCE SPECTROSCOPY OF TRANSITION ELEMENTS: EXPERIMENTAL SETUP AND PRELIMINARY RESULTS ON CR3+ IN SILICATE GLASSES - Quérel G.; Reynard B. (My University, 1996)
Luminescence spectroscopy of transition elements can provide useful information on their binding properties, local environment and crystal-field stabilization energies in various materials. In order to investigate the evolution of these properties with pressure, we have adapted our Raman microspectrometer for high-pressure luminescence spectroscopy in a diamond anvil cell in the spectral range 450–900 nm.We present spectroscopic results obtained on four silicate glasses doped with 0.1–0.3 mole% Cr3+. Firstly, ambient pressure spectra are characterized by the presence of a broad fluorescence band near 11,500 cm−1 which arises from a 4T2 → 4A2 transition and weak narrow bands near 14,700 cm−1 arising from the 2E level. The position of the 4T2 → 4A2 band depends nearly-linearly upon the excitation wavelength, suggesting the presence of a single site population within the glass.Secondly, a 20% Na2O–80% SiO2 glass has been compressed up to 15 GPa. Up to ∼ 9 GPa, the spectroscopic evolution is consistent with the increase of the average Dq due to the compression of CrO bonds. At higher pressures, it suggests the occurrence of a structural reorganization of the glass. Upon decompression, the peak positions, linewidths and relative intensities evolve in an irreversible manner, pointing the need for in situ measurements in order to understand the high-pressure behaviour of Cr3+ and transition elements in general. The comparison of our data with previous high-pressure spectroscopic measurement on Cr3+ at high-pressure suggests that the CrO bond is more compressible in glasses than in crystalline oxides, which is consistent with a decrease of the mineral/melt partition coefficient of Cr at high pressure.